Hang on St. Christopher - McKinty, Adrian (McKinty, Adrian. Detective Sean Duffy novel, 2025)
"Rain slicked streets, riots, murder, chaos. It's July 1992 and the Troubles in Northern Ireland are still grinding on after twenty-five apocalyptic years. Detective Inspector Sean Duffy got his family safely over the water to Scotland, to "Shortbread Land". Duffy's a part-timer now, only returning to Belfast six days a month to get his pension. It's an easy gig, if he can keep his head down. But then a murder case falls into his lap while his protege is on holiday in Spain. A carjacking gone wrong and the death of a solitary, middle-aged painter. But something's not right, and as Duffy probes he discovers the painter was an IRA assassin. So, the question becomes: Who hit the hitman and why? This is Duffy's most violent and dangerous case yet and the whole future of the burgeoning "peace process" may depend upon it. Based on true events, Duffy must unentangle parallel operations by the CIA, MI5 and Special Branch. Duffy attempts to bring a killer to justice while trying to keep himself and his team alive as everything unravels around them. They might not all make it out of this one."-- Amazon.